When Down Is Up: Heterochromatin, Nuclear Organization and X Upregulation. - Makki, R.; Meller, V.H. (Cells, 2021)
Organisms with highly differentiated sex chromosomes face an imbalance in X-linked gene dosage. Male Drosophila solve this problem by increasing expression from virtually every gene on their single X chromosome, a process known as dosage compensation. This involves a ribonucleoprotein complex that is recruited to active, X-linked genes to remodel chromatin and increase expression. Interestingly, the male X chromosome is also enriched for several proteins associated with heterochromatin. Furthermore, the polytenized male X is selectively disrupted by the loss of factors involved in repression, silencing, heterochromatin formation or chromatin remodeling. Mutations in many of these factors preferentially reduce male survival or enhance the lethality of mutations that prevent normal recognition of the X chromosome. The involvement of primarily repressive factors in a process that elevates expression has long been puzzling. Interestingly, recent work suggests that the siRNA pathway, often associated with heterochromatin formation and repression, also helps the dosage compensation machinery identify the X chromosome. In light of this finding, we revisit the evidence that links nuclear organization and heterochromatin to regulation of the male X chromosome.